Low Dose Bupivacaine plus Fentanyl in Subarachnoid Block for Caesarean Section (Delta Medical College Journal, 2016)
Background: Spinal anaesthesia induced hypotension, a common problem during caesarean section, is associated with maternal nausea and vomiting and the risk of neonatal acidosis. Low dose local anaesthetic combined with opioids spinal anaesthesia better preserves maternal haemodynamic stability, resulting in equally efficacious anaesthesia.Objectives: To investigate whether this synergistic action could be used to provide effective anaesthesia while preventing hypotension during caesarean operation.Materials and method: This prospective study included 60 pregnant mothers scheduled for caesarean operation who were then divided into two groups (thirty in each). Group-A received a spinal injection of 12.5 mg of standardized 0.5% hyperbaric bupivacaine and group-B received 8 mg of 0.5% hyperbaric bupivacaine with 20 ?gm fentanyl. Hypotension was defined as the systolic blood pressure drops below 90 mm of Hg or a decrease of systolic blood pressure 25% from pre anaesthesia level and hypotension was treated with a bolus of 5 to 10 mg of intravenous ephedrine. The quality of anaesthesia and postoperative analgesia were evaluated.Results: The mean time required to reach peak sensory level was earlier in group-B than group-A and was statistically significant (p